MATHEMATIC DISPOSITION OF STUDENTS ON THE APLICATION OF ETHNOMATHEMATICS INTERACTIVE MATHEMATHICS LEARNING - M. Ardiansyah; Mohamad Lutfi Nugraha; Budi Santoso (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2023)
This study to describe the mathematical disposition of students on the application of ethnomtematics in interactive mathematics learning in schools. The approach used is qualitative and quantitative with descriptive types. The research subject one person mathematics educator work and 30 students of Perti Jakarta Islamic Vocational High School. Data were obtained through interviews and filling out questionnaires with a Likert scale type. The results obtained indicate that the application of Ethnomathematics can have a positive influence on mathematics learning in schools. Based on research findings from an interview with a mathematics educator, it has been discovered that the implementation of ethnomathematics in mathematics education can enhance students' interest and self-confidence in the interactive mathematics learning process. This approach is popular among students. The findings of the research are further supported by the results of a mathematical disposition questionnaire, which was assessed from various aspects. First, students displayed a good level of confidence in the mathematics learning process, with an average score of 2.33. This indicates that the application of an ethnomathematical approach in their education fosters a sense of confidence and self-assuredness among students when dealing with mathematical concepts. Second, in terms of diligence and perseverance in learning mathematics, the average score was 1.98, considered fairly good. This aspect suggests that students agree with the utilization of the ethnomathematical-based approach, which motivates them to be more diligent and persistent in their mathematical studies at school. These results highlight the positive impact of ethnomathematics on students' interest and self-confidence in interactive mathematics learning.